IMPROVING THE PROFESSIONAL TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS THROUGH THE DEVELOPMENT OF FUNCTIONAL LITERACY (Universal International Scientific Journal, 2026)
This article examines the theoretical and methodological foundations for improving the professional training of future primary school teachers through the development of functional literacy. The relevance of this problem is substantiated in the context of the modernization of the higher pedagogical education system and the transition to a competency-based teaching model. The essence of functional literacy is revealed as an integrative personal quality that ensures the ability to effectively apply knowledge in professional activities. Pedagogical conditions that contribute to the development of functional literacy in students majoring in pedagogy are identified, and the results of an analysis of the effectiveness of implementing practice-oriented teaching technologies are presented. A conclusion is drawn regarding the need for a systematic update of the content and methods of training future teachers.
Keywords: Professional training; future primary school teachers; functional literacy